2021
DOI: 10.1097/mph.0000000000002266
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin-induced Pneumonitis in a Child Treated With Nintedanib: Report of the First Case in a Childhood

Abstract: Pulmonary fibrosis caused by bleomycin-induced pneumonia (BIP) is the most important side effect limiting the use of bleomycin and is mainly treated with corticosteroids. However, 1% to 4% of patients do not respond to corticosteroid therapy. Idiopathic pulmonary fibrosis and BIP develop by similar pathophysiological mechanisms. Nintedanib is a tyrosine kinase inhibitor used successfully in the treatment of idiopathic pulmonary fibrosis and there is no information about its use in BIP treatment. Here, we would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The first case about the use of nintedanib in bleomycin‐induced pneumonia (BIP) was reported by Gundogan et al A 13‐year‐old boy with Hodgkin lymphoma who developed BIP with respiratory failure despite corticosteroid therapy after chemotherapeutic agents including bleomycin was presented. The patient was successfully treated with nintedanib 44 . The dose of nintedanib administered in this case was 200 mg/day.…”
Section: Management Of the Pulmonary Fibrosis In Childrenmentioning
confidence: 97%
See 3 more Smart Citations
“…The first case about the use of nintedanib in bleomycin‐induced pneumonia (BIP) was reported by Gundogan et al A 13‐year‐old boy with Hodgkin lymphoma who developed BIP with respiratory failure despite corticosteroid therapy after chemotherapeutic agents including bleomycin was presented. The patient was successfully treated with nintedanib 44 . The dose of nintedanib administered in this case was 200 mg/day.…”
Section: Management Of the Pulmonary Fibrosis In Childrenmentioning
confidence: 97%
“…26 In this study eligible children and with nintedanib. 44 The dose of nintedanib administered in this case was 200 mg/day. In a similar case of ours, nintedanib given as BIP treatment failed in an 11-year-old child whose respiratory functions were so poor that he could not perform PFT.…”
Section: Management Of the Pulmonary Fibrosis In Childrenmentioning
confidence: 98%
See 2 more Smart Citations
“…Nintedanib has been approved for the treatment of idiopathic pulmonary fibrosis (IPF) in many countries, and several clinical trials have proven its effectiveness and safety in the treatment of IPF 16 17. Recently, Gundogan et al also reported a 13-year-old lymphoma patient treated with a bleomycin-containing chemotherapy regimen who developed bleomycin-induced pneumonia that was successfully treated with nintedanib 18. Moreover, nintedanib also showed antitumour effects in some reports 19 20…”
Section: Introductionmentioning
confidence: 99%